Perencanaan Rumah Susun di Kabupaten Tolitoli - Dwi Purnomo (PT FORMOSA CENDEKIA GLOBAL, 2022)
The purpose of this research is to design a condominium building with a modern architecture approach. The method used in this study is a qualitative descriptive method where in this method is carried out through a search for existing problems in the form of facts that occur in the field to identify the fulfillment of a place to live for low-income people. The data obtained are then analyzed to determine the need for the construction of flats with a Modern Architecture concept approach. In addition, the building is also more impressive with the use of fabricated materials, there are many openings in the building that function as ventilation, natural lighting, and the building is more impressive open so that the view from the building is very good. The total area of the site or location for the construction of this flat is 12,000 m² with planned BC.